(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
Cloud computing is a technology that is both efficient and cost-effective, thanks to its low mainte nance requirements. This paper implemented a approach is used to share group resources across cloud users. Regretta bly, as a result of the frequent differences in participation, the issue of sharing information in a multi-owner manner while also preserving privacy and information from a trusted cloud continues to be a challenging one. During the course we put into place a safe method of data sharing among mul tiple owners using the Diffe- Hellman algorithm that are cloud-based and applicable to rotating groups. By leveraging techniques like as group signature and dynamic broadcast encryption, any user of the cloud has the ability to anony mously share data with other users. In the meanwhile, the number of users whose access has been revoked does not have any impact on the storage overhead or encryption com putation costs associated with our system. In addition, em ploy rigorous proofs to investigate the scheme’s level of safety, and conduct tests to verify the scheme’s usefulness.